EFFECT OF NAUCLEA ORIENTALIS (BAKMI) IN THE FORM OF PARISHEKA SWEDA AND YOGA VASTI IN THE TREATMENT OF GRUDHRASI (SCIATICA) - H.A.Tilaka Malini,; E.R.H.S.S.Ediriweera,; W.D.Ratnasooriya, (International Journal of Ayurveda and Pharma Research, 2020)
Authentic texts describe Grudhrasi under Vata Roga. One of its main clinical features is a pain that radiates from Sphik Pradesha (buttocks) to Pada (foot). It can be corelated with sciatica. Piyusharnava, describes that Parisheka Sweda using Nauclea orientalis (Bakmi) as a treatment for Katigaha (Lumbago). Vasti Karma using N. orientalis (Bakmi) is in practice and Vasti is the best treatment for Vata Roga. Seventy-five patients suffering from Grudhrasi (sciatica) were treated with Parisheka Sweda, Vasti and combined therapy. Parisheka Sweda was carried out for a period of seven days. Vasti was performed as Yoga Vasti. Both therapies were carried out in combined therapy group; namely, Parisheka Sweda followed by Yoga Vasti. All three groups showed statistically significant reduction in all the symptoms but there was no statistical difference between groups. Parisheka Sweda and Yoga Vasti using Nauclea orientalis (Bakmi) can be recommended as an effective treatment for Grudhrasi (sciatica).